1996
DOI: 10.1046/j.1471-4159.1996.66030980.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Drebrin of the Actin‐Bundling Activity of Brain Fascin, a Protein Localized in Filopodia of Growth Cones

Abstract: The purification of drebrin, an actin‐binding protein that is specifically expressed in embryonic rat brain, was described previously. During the purification of drebrin, we found that an actin‐binding protein of 54 kDa was also expressed at high levels in embryonic brain, and this protein was identified by immunoblotting as fascin. To explore the roles of fascin in brain development, we purified fascin from brains of infant rats and characterized it. We found that the actin‐binding activity of fascin was stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 44 publications
(48 reference statements)
6
74
0
1
Order By: Relevance
“…Positive correlation between drebrin content in each spine and its PSD length supports this idea. Drebrin is thought to be involved in the dynamics of actin cytoskeleton through inhibition of actin-myosin interaction Cheng et al, 2000) and competition for other actin-binding proteins, including tropomyosin, α-actinin (Ishikawa et al, 1994), and fascin (Sasaki et al, 1996). The alteration of actin dynamics via drebrin A may enable enlargement of spines by mechanism yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation between drebrin content in each spine and its PSD length supports this idea. Drebrin is thought to be involved in the dynamics of actin cytoskeleton through inhibition of actin-myosin interaction Cheng et al, 2000) and competition for other actin-binding proteins, including tropomyosin, α-actinin (Ishikawa et al, 1994), and fascin (Sasaki et al, 1996). The alteration of actin dynamics via drebrin A may enable enlargement of spines by mechanism yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Second, expression data are strongly suggestive of a role for fascin in neuronal morphogenesis. The localization of fascin to growth cone filopodia (Sasaki et al, 1996;Cohan et al, 2001) suggested to the latter authors that fascin promotes "the linear structure and dynamics of filopodia." The failure of singed-mutant neurites to maintain a straight trajectory and uniform caliber provides compelling experimental support for this hypothesis.…”
Section: Unsuspected Neuronal Phenotypes Revealed In Vitromentioning
confidence: 99%
“…It does so by interfering with the actin binding and bundling activities of fascin, ␣-actinin, and tropomyosin (31,32). A similar mechanism might underlie the p116…”
Section: Ripmentioning
confidence: 99%